Morphological Indexes: Can They Predict Lupus Nephritis Outcomes? A Retrospective Study - Navarro, David (2019)
Introduction: Lupus nephritis is a serious complication of systemic lupus erythematosus. Currently, therapy is guided by findings in the renal biopsy, following the International Society of Nephrology / Renal Pathology Society classification. Austin and Hill’s histomorphological indexes are not routinely obtained. In this retrospective single-centre study, we aimed to analyze the importance and applicability of the different morphological indexes in predicting response to treatment and prognosis.Material and Methods: Patients with kidney biopsy demonstrating lupus nephritis from the 2010 – 2016 period were included. We analyzed their demographic data, comorbidities, clinical presentation and laboratorial evaluation at the time of renal biopsy. We evaluated the following outcomes: clinical remission, renal function and proteinuria at end of follow-up. Histologic analysis was performed using the International Society of Nephrology / Renal Pathology Society classification and the morphological indexes described by Austin (Activity and Chronicity) and Hill. Univariate and multivariate statistical analysis was performed using STATA software.Results: We analyzed 46 biopsy-proven lupus nephritis cases, with a median follow-up of 31.9 (13.2 – 45.6) months. Based on biopsy findings, 35 patients were started on immunosuppressive therapy. We observed that Class IV patients had, at presentation, lower estimated glomerular filtration rate (67.3 vs 94.6 mL/min; p = 0.02), higher proteinuria (4.26 vs 2.37 g/24 hours; p = 0.02) and a non-significantly higher C3 consumption (58.9 vs 77.4 mg/dL; p = 0.06). We did not observe correlations between International Society of Nephrology / Renal Pathology Society classification and the outcomes at the end of follow-up. In contrast, both the Hill biopsy index and Austin’s Chronicity index were correlated with renal function and proteinuria at the end of follow-up. Austin’s Activity index correlated with the immunological findings (C3, C4 and anti-dsDNA) at presentation.Discussion: Because clinical activity poorly correlates with histologic activity, histological findings are fundamental when assessing patients with suspected lupus nephritis. The most recent International Society of Nephrology / Renal Pathology Society report supports the European League Against Rheumatism guidelines, encouraging the adoption of histomorphological indexes when evaluating lupus nephritis. Our data, showing a correlation between the renal outcomes and the indexes described by Austin and Hill, supports this view.Conclusion: The histomorphological indexes in lupus nephritis are easily obtainable, can predict renal outcomes and may help in the management of such patients.